Analisis Manajemen Pendidikan Karakter di Pondok Pesantren: Studi di Pondok Pesantren Bustanul ‘Ulum Lampung Tengah - Syarif Maulidin; Deni Januar Darma Surya Siregar; Prayitno Prayitno (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This study focuses on analyze of character education management at Islamic Boarding School Bustanul 'Ulum Jayasakti Anak Tuha Lampung Tengah. The importance of character education has been widely acknowledged in shaping well-rounded individuals with strong moral values, in line with Islamic teachings at Islamic boarding school. The purpose of this research is to analyze how Bustanul ‘Ulum Islamic Boarding School implemented character education through systematic management practices. This type of research is qualitative research with case study approach. The data were obtained through interview, observation, and documentation. The research subjects were selected using purposive sampling involving interviews with key stakeholders, including the pesantren’s management, teachers, and students. The findings reveal that the pesantren has successfully integrated character education into its curriculum, daily activities, and spiritual practices. Through a collaborative process, the management ensures the alignment of character education with national educational standards, fostering a holistic development of students. Regular evaluation and supervision play a crucial role in assessing the effectiveness of the programs. The study concludes that the management of character education at Bustanul ‘Ulum Islamic Boarding School Jayasakti serves as a model for other Islamic boarding schools, demonstrating the importance of structured, consistent efforts in character development for students